Ecdysteroids from the underground parts of Rhaponticum acaule (L.) DC. (December 2020) - Zughdani, Mhmuod; Yusufoğlu, Hasan Soliman; Ekiz, Güner; Linden, Anthony; Çalış, İhsan
Abstract: In addition to two known ecdysteroids, 20-hydroxyecdysone and turkesterone, three previously undescribed stigmastane-type ecdysteroids were isolated from the underground parts of Rhaponticum acaule (L.) DC. by chromatographic techniques (CC, VLC, MPLC). The structures of the compounds were established by chemical (acetylation) and spectroscopic methods including UV, IR, HRMS, 1D-NMR: 1 H-NMR, 13 C-NMR, DEPT-135. and 2D-NMR: COSY, NOESY, HSQC, HMBC. Two compounds were isolated as an isomeric mixture and each of them was purified and converted to the corresponding acetylated derivative. Based on all of the evidence, the structures of three undescribed stigmastane-type ecdysteroids were established as 2β, 3β, 11α, 20β, 22α, 24, 28-heptahydroxy-6-oxo-stigmast-7-en-25, 29-lactone and the cyclic 22, 29-hemiacetals 22 R and 22 S stigmast-7-en-29-al, 2β, 3β, 11α, 20α, 22, 28-hexahydroxy-6-oxo, and the trivial names acaulesterone and rhapocasterones A and B are suggested, respectively. The structures and absolute configurations of 20-hydroxyecdysone and cyclic-22, 29-hemiacetal-22 R -stigmast-7-en-29-al, 2β, 3β, 11α, 20α, 22, 28-hexahydroxy-6-oxo were confirmed by X-ray crystal-structure analyses of their acetyl derivatives. Graphical abstract: Three undescribed stigmastane-type ecdysteroids were isolated from the underground parts of Rhaponticum acaule (L.) DC. Image 1 Highlights: Phytochemical investigation on the roots of Rhaponticum acalue (L.) DC. was performed. Three undescribed stigmastane-type ecdysteroids have been identified. The absolute configurations of some compounds were confirmed crystallographically.